(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article discusses the importance of diagnosing and analyzing the business activities of a commercial organization in an unstable economy. Despite the desire to make a profit, it is initially important for every commercial organization to provide its own expenditure items. The author provides a description of each type of analytical work, as well as reveals possible ways to optimize financial flows using the examples given.